Efeito do extrato etanólico de folhas de Passiflora edulis sobre a ativação de macrófagos e formação de produtos finais de glicação avançada (AGEs) em ratos diabéticos - Martins, Carolina Fernandes Ribas (2013)
The high production of advanced glycation end-products (AGEs) have been identified as reponsible for the impairment of immunological function, leading to an increase on susceptibility of infections on diabetic patients. This mechanisms can involve the NADPH oxidase activation, decrease of phagocytic capacity, interactions between the AGEs produced and important macromolecules to the immune function or with the receptor for advanced glycation end-products (RAGEs), increasing the production of inflammatory cytokines. The therapeutic use of leaves of several species of Passilfora is common in folk medicine in several countries, including Brazil. Nevertheless, some scientific information regarding the use of leaf extracts of Passiflora edulis in the treatment of diabetes and its complications, remains still unclear. Thus, the objective of this present work is to evaluate the effects of this extract on phagocytic capacity on macrophages in diabetic rats. Wistar male rats (300 ± 25g) were treated with alloxan (120 mg/kg body weight dissolved in saline 0,9% intraperitoneal). The ethanolic extract was obtained by maceration in wateralcohol solution 70% (v/v) followed by evaporation under reduced pressure and lyophilization. After this process, the extract was diluted in water and administered by gavage (200 mg of dry ethanolic extract/kg body weight), during 8 weeks after the diabetes induction. The rats were anesthetized and blood sample was collected by cardiac puncture to obtain the sérum for the determination of glucose by enzimatic colorimetric method and determination of AGEs levels by fluorescence. The concentration of fructosamine was determined by colorimetric method in serum. The cell activation was determined through the production of ROS and phagocytic capacity of peritoneal macrophages, activated with opsonized Candida albicans (ATCC69548). The production of ROS was determined by chemiluminescence activated with luminol. The evaluation of phagocytic capacity was performed through the incubation of the phagocytes with Candida albicans internalized. The microbicide activity was determined by evaluating the viability of phagocyted yeast